Effects of bisphenol A on metabolism and evidences of a mode of action mediated through endocrine disruption. (5th November 2018) - Le Magueresse-Battistoni, Brigitte; Multigner, Luc; Beausoleil, Claire; Rousselle, Christophe
Abstract: Based on rodent studies after prenatal and/or perinatal or adult exposure, there is now evidence that BPA may increase metabolic disturbances eventually leading to type-2 diabetes development via an ED MoA. In particular, BPA has been shown to alter insulin synthesis and/or release by pancreatic β-cells, and insulin signaling within insulin-sensitive organs (i.e., liver, muscle, adipose tissues). This resulted in variations in the expression of specific hepatic or adipose tissue markers, which are indicative of a state of insulin resistance. These effects are considered by experts to be hallmarks of adverse hormonal effects, each leading to insulin resistance within the different insulin-sensitive tissues. Although epidemiological studies are inconclusive, these effects are considered relevant for humans, because similarities exist in homeostatic regulation of insulin production and sensitivity between rodents and humans and because evidence was also shown through in vitro experimental data using human cells or tissues. Highlights: BPA decreases insulin synthesis and secretion, after prenatal or adult exposure. BPA decreases insulin action, after prenatal, perinatal and adult exposure. There is good evidence of BPA toxicity on pancreatic β -cells. Estrogen receptor mechanism (β/α or GPR30 types) may be involved. Epigenetic mechanisms are also suggested.